Uncovering the cellular and molecular changes in tendon stem/progenitor cells attributed to tendon aging and degeneration. Issue 6 (22nd July 2013) - Kohler, Julia; Popov, Cvetan; Klotz, Barbara; Alberton, Paolo; Prall, Wolf Christian; Haasters, Florian; Müller‐Deubert, Sigrid; Ebert, Regina; Klein‐Hitpass, Ludger; Jakob, Franz; Schieker, Matthias; Docheva, Denitsa
Summary Although the link between altered stem cell properties and tissue aging has been recognized, the molecular and cellular processes of tendon aging have not been elucidated. As tendons contain stem/progenitor cells (TSPC), we investigated whether the molecular and cellular attributes of TSPC alter during tendon aging and degeneration. Comparing TSPC derived from young/healthy (Y‐TSPC) and aged/degenerated human Achilles tendon biopsies (A‐TSPC), we observed that A‐TSPC exhibit a profound self‐renewal and clonogenic deficits, while their multipotency was still retained. Senescence analysis showed a premature entry into senescence of the A‐TSPC, a finding accompanied by an upregulation of p16INK4A. To identify age‐related molecular factors, we performed microarray and gene ontology analyses. These analyses revealed an intriguing transcriptomal shift in A‐TSPC, where the most differentially expressed probesets encode for genes regulating cell adhesion, migration, and actin cytoskeleton. Time‐lapse analysis showed that A‐TSPC exhibit decelerated motion and delayed wound closure concomitant to a higher actin stress fiber content and a slower turnover of actin filaments. Lastly, based on the expression analyses of microarray candidates, we suggest that dysregulated cell–matrix interactions and the ROCK kinase pathway might be key players in TSPC aging. Taken together, we propose that during tendon aging and degeneration, the TSPC pool is becoming exhausted in terms of size and functional fitness. Thus, our study provides the first fundamental basis for further exploration into the molecular mechanisms behind tendon aging and degeneration as well as for the selection of novel tendon‐specific therapeutical targets.